2021
DOI: 10.7150/thno.54630
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop trans-skull ultrasound hyperthermia leads to improved drug delivery from thermosensitive drugs and promotes changes in vascular transport dynamics in brain tumors

Abstract: Effective drug delivery in brain tumors remains a major challenge in oncology. Although local hyperthermia and stimuli-responsive delivery systems, such as thermosensitive liposomes, represent promising strategies to locally enhance drug delivery in solid tumors and improve outcomes, their application in intracranial malignancies remains unexplored. We hypothesized that the combined abilities of closed-loop trans-skull Magnetic Resonance Imaging guided Focused Ultrasound (MRgFUS) hyperthermia with those of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Particularly, when comparing different drug delivery approaches with such different pharmacokinetics and drug release mechanisms as free drug, traditional liposomes, or intravascular releasing thermosensitive liposomes. Most commonly, tumor drug accumulation following thermosensitive liposome administration is assessed immediately post heating [27,36,59,60]. Here, immediately post heating, VRL concentrations in the tumor are significantly higher when administered as ThermoVRL compared to the administration as free drug as well as a nonthermosensitive liposome formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, when comparing different drug delivery approaches with such different pharmacokinetics and drug release mechanisms as free drug, traditional liposomes, or intravascular releasing thermosensitive liposomes. Most commonly, tumor drug accumulation following thermosensitive liposome administration is assessed immediately post heating [27,36,59,60]. Here, immediately post heating, VRL concentrations in the tumor are significantly higher when administered as ThermoVRL compared to the administration as free drug as well as a nonthermosensitive liposome formulation.…”
Section: Discussionmentioning
confidence: 99%
“…(d) Thermal field induced by a flat LIPUS transducer (T. Hornsby, Jakhmola, et al, 2021). (e) The temperature rise in ROI caused by FUS considering a simple binary (on–off) controller for different perfusion parameters incorporated into the BHTE (Kim et al, 2021).…”
Section: Computational Models For Tus Applicationsmentioning
confidence: 99%
“…In addition, researchers have not adequately evaluated the dependence of parameters of tumor tissue, NPs, and chemotherapeutic agents on both thermal and nonthermal effects induced by US. A few studies have recently attempted to address some of these issues limited to US thermal effects in specific drug delivery applications (Gasselhuber et al, 2012; Kim et al, 2021; Rezaeian et al, 2019; Zhan et al, 2019). However, there is still a long way to achieve a comprehensive theoretical model that integrates the applicable physics at all relevant scales.…”
Section: Introductionmentioning
confidence: 99%
“…While the use of carrier vehicles including MBs, liposomes, and nanoparticles to deliver chemotherapeutics offers protection from systemic side effects, it limits release of the agent at the target site (particularly in CNS tumors) and may result in subtherapeutic local drug levels [ 110 ]. Preclinical studies have demonstrated the ability of MRgFUS to increase the targeted release of therapeutic agents from drug delivery vehicles through hyperthermia, stable cavitation, and radiation forces [ 111 – 113 ].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Preclinical studies have demonstrated the ability of MRgFUS to increase the targeted release of therapeutic agents from drug delivery vehicles through hyperthermia, stable cavitation, and radiation forces [ 111 – 113 ]. In addition to improving delivery of carrier vehicles through the BBB in rodents, MRgFUS has been successfully applied in a trans-skull model to generate controlled hyperthermia and effectively release thermosensitive drugs in glioma [ 110 , 114 ]. Other studies have examined the frequency and duration of FUS for this purpose, with some results suggesting high intensity bursts may be optimal [ 115 117 ].…”
Section: Preclinical Studiesmentioning
confidence: 99%